Expert guidance on prophylaxis and treatment of dermatologic adverse events with Tumor Treating Fields (TTFields) therapy in the thoracic region - Anadkat, Milan J.; Lacouture, Mario; Friedman, Adam; Horne, Zachary D.; Jung, Jae; Kaffenberger, Benjamin; Kalmadi, Sujith; Ovington, Liza; Kotecha, Rupesh; Abdullah, Huda Ismail; Grosso, Federica (Frontiers in Oncology, 2023)
Tumor Treating Fields (TTFields) are alternating electric fields that disrupt cancer cell division, delivered via wearable transducer arrays placed on or near the tumor site. TTFields therapy is a first-in-class treatment that is approved for use in newly diagnosed glioblastoma, recurrent glioblastoma, and malignant pleural mesothelioma (MPM). TTFields therapy is also being investigated in several ongoing and completed clinical trials in non-small cell lung cancer (NSCLC), brain metastases from NSCLC, pancreatic cancer, ovarian cancer, hepatocellular carcinoma, and gastric adenocarcinoma. Because TTFields therapy is well tolerated and delivery is locoregional, there is low risk of additive systemic toxicity when used with other cancer treatment modalities. The most common adverse event (AE) associated with TTFields therapy is mild-to-moderate skin events, which can be treated with topical agents and may be managed without treatment interruptions. Currently there are no guidelines for oncologists regarding the management of TTFields therapy-related skin AEs in the thoracic region, applicable for patients with MPM or NSCLC. This publication aims to provide guidance on preventing, minimizing, and managing dermatologic AEs in the thoracic region to help improve patient quality of life and reduce treatment interruptions which may impact outcomes with TTFields therapy.